ANALISIS TINGKAT KESEHATAN BANK BERDASARKAN METODE CAMELS DAN METODE RGEC - AJI PERMANA, BAYU Aji (Jurnal Akuntansi AKUNESA, 2012)
Bank soundness analysis is a form of embodiment of the procedure to find a bank considered healthy or not. Basically banking policies issued and implemented by Bank Indonesia is intended to create and maintain good health, both individually or as a system. With bank soundness of analysis is expected to know which banks are healthy and which banks are not . The method used is a qualitative descriptive approach. CAMELS method has weaknesses. Factor assessment method in CAMELS does not produce a uniform conclusion. To overcome the drawbacks of CAMELS method, Bank Indonesia sets new rules by using Risk-based Bank Rating. Bank soundness analysis using Risk-based Bank Rating more emphasize on risk profile. Keywords: CAMELS and Risk-based Bank Rating .